Assessing the Characteristics of Vaginal Discharge: A Critical Perspective on Women’s Health (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Vaginal discharge is a common gynecological problem of varying etiol ogies affecting women's health. This study aimed to assess the characteristics of vaginal discharge in women and aimed to bridge the gap by assessing knowledge, attitude and practice related to menstrual and puerperal hygiene. Materials and methods: This cross-sectional study was conducted at the outpatient department of Obstetrics and gynecology at Chattagram Maa-O-Shishu Hospital Medical College, from July to December 2018 and included 91 women presenting with vaginal discharge and related problems. Data were collected through pretested semi structured questionnaires, clinical examinations, High Vaginal Swab (HVS) Pap Smear and Urine Routine and Microscopic Examination (RME) and Culture Sensitivity (C/S). Results: The majority of participants were in the 20-24 (34.07%) and 25-29 (26.37%) age groups, predominantly married (90.11%), largely housewives (75.82%) with education below higher secondary level (59.34%). Over half (51.65%) were overweight. Oral contraceptives were the most common contraceptive method (35.16%). Good menstrual hygiene and puerperal hygiene practiced by 43.96% participants and poor menstrual and puerperal hygiene by 56.04%. HVS results showed Candida and mixed infections (10.99% each) Trichomonas (8.79%) and Bacterial Vaginosis (BV) (3.30%). Pap Smear indicated a range of infection severity and Urine RME& C/S revealed infection rate 30.77%. Conclusion: The study highlights the need for accurate diagnosis and comprehensive reproductive healthcare and practice of healthy menstrual and puerperal hygiene to manage vaginal discharge effectively. It emphasizes the significance of various factors such as lifestyle, educational background and clinical characteristics for accurate diagnosis and treatment.Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 91-96